Optimization Circuit Based Buck-Boost Converter for Charging the Solar Power Plant - Rohana Rohana; Suwarno Suwarno (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper discusses the optimization circuit based buck-boost converter for charging a battery from solar panel modules. The combination of the circuit buck-bust converter and a step-up current can increase the percentage of battery chargers. The method used in the optimization of solar power plants by increasing the output current from the solar panel to be optimized for battery charging, so it does not requires time and the batteries are safe. This is because sunlight can be used when bright about 4-5 hours per day. By increasing the output current of the current produced solar modules can accelerate the battery charging time. The combination of using the voltage stabilizer can produce a steady output voltage and current riser, although the voltage to an output of the solar panels is quite small (± 6 volts), can optimize the charger works well. By combining between the voltage stabilizer and a step-up current is obtained that the incoming voltage to the battery at 12,4V the current rise of 21.5% for a 12V battery, 7Ah, whereas the incoming voltage to the battery at 12,1V the current rise 10.99% for battery 12V, 120Ah. This study shows that the current rise is already above 10%.